Empowering Women as Leaders in Pediatric Anesthesiology: Methodology, Lessons, and Early Outcomes of a National Initiative. (13th September 2021) - Schwartz, Jamie McElrath; Markowitz, Scott D.; Yanofsky, Samuel D.; Tackett, Sean; Berenstain, Laura K.; Schwartz, Lawrence I.; Flick, Randall; Heitmiller, Eugenie; Fiadjoe, John; Lee, Helen H.; Honkanen, Anita; Malviya, Shobha; et al.
Abstract : Research has shown that women have leadership ability equal to or better than that of their male counterparts, yet proportionally fewer women than men achieve leadership positions and promotion in medicine. The Women's Empowerment and Leadership Initiative (WELI) was founded within the Society for Pediatric Anesthesia (SPA) in 2018 as a multidimensional program to help address the significant career development, leadership, and promotion gender gap between men and women in anesthesiology. Herein, we describe WELI's development and implementation with an early assessment of effectiveness at 2 years. Members received an anonymous, voluntary survey by e-mail to assess whether they believed WELI was beneficial in several broad domains: career development, networking, project implementation and completion, goal setting, mentorship, well-being, and promotion and leadership. The response rate was 60.5% (92 of 152). The majority ranked several aspects of WELI to be very or extremely valuable, including the protégé-advisor dyads, workshops, nomination to join WELI, and virtual facilitated networking. For most members, WELI helped to improve optimism about their professional future. Most also reported that WELI somewhat or absolutely contributed to project improvement or completion, finding new collaborators, and obtaining invitations to be visiting speakers. Among those who applied for promotion or leadership positions, 51% found WELI to be somewhat or absolutely valuable to their application process, and 42% found the same in applying for leadership positions. Qualitative analysis of free-text survey responses identified 5 main themes: (1) feelings of empowerment and confidence, (2) acquisition of new skills in mentoring, coaching, career development, and project implementation, (3) clarification and focus on goal setting, (4) creating meaningful connections through networking, and (5) challenges from coronavirus disease 2019 (COVID-19) and the inability to sustain the advisor-protégé connection. We conclude that after 2 years, the WELI program has successfully supported career development for the majority of protégés and advisors. Continued assessment of whether WELI can meaningfully contribute to attainment of promotion and leadership positions will require study across a longer period. WELI could serve as a programmatic example to support women's career development in other subspecialties.